PENGEMBANGAN SISTEM INFORMASI MONITORING PRAKERIN BERBASIS ANDROID DI SMKN 2 BARRU - Irham Halik; Purnamawati; Abdul Muis Mappalotteng (Universitas Negeri Makassar, 2023)
This study aims: (1) to produce an Android-based internship monitoring information system, and (2) to determine the performance of an Android-based internship monitoring information system. This study used the Research and Development research method which was carried out at SMKN 2 Barru. The research data was obtained by giving a questionnaire to 30 respondents divided into 20 productive teachers and 10 industrial partners. The data analysis technique used is percentage descriptive analysis. The results of the analysis found an Android-based internship monitoring information system. The test results using the Black Box method on the system show that the system has good functionality, all functions can work properly and have met the requirement specifications. The test results show that the information system has been acceptable to users and can be used as a medium to find information about internship activities. For future Android-based apprentice monitoring information system developers, it is expected that all SMK in Barru Regency can use it. Recommendations for researchers who are interested in studying and studying more broadly should use different development and application methods.